How Can Governmental Incentives Inspire Youth to Be More Engaged in Environmental Protection? An Analysis of Factors Affecting Djiboutian Young People’s Engagement Toward the Environment - Aden, Kadir (Public Governance, Administration and Finances Law Review, 2023)
During the past years, environmental protection and adopting countermeasures against climate change have been on the agenda of many East African countries, as well as western nations, although a common challenge confronted by policymakers is directing young people’s interest toward the environment. Therefore, the purpose of this paper is to explore the impact of certain factors that can be adopted by government bodies as a strategy to make youth more engaged in environmental activities. An electronic questionnaire was completed by Djiboutian young people from February 2022 to late June 2022. We retrieved 440 out of 500 questionnaires; a structural equation model was subsequently employed to assess the effects of government rewards, interactions, capacity building and favourable policies on youth engagement. According to the results, all the factors demonstrated a positive impact on youth engagement; consequently, we conclude that young people have tendencies to engage in activities that revolve around environmental issues when there is a reward system in place. Likewise, establishing an interactive platform that accommodates young people’s opinions while the government provides reasonable feedback will stimulate engagement. Reasonably, embracing policies in favour of the environment will depict the government as an effective, responsible leader, retroactively influencing young people’s perceptions. On the other hand, allowing youths to participate in the process of policies formulation will guarantee a long-term societal engagement, since, pragmatically speaking, these adopted policies will eventually influence their future; at the same time, we conclude that providing proper training and building young people’s capacity will provide them with fundamental personal skills, while simultaneously enhancing their sustainable attitude to respond adequately to environmental challenges consequently assisting the national government with their environmental endeavours. Finally, the following paper contributes to the relevant existing body of literature, by providing empirical evidence on different types of government initiatives that could make young people more engaged and inclined in environmental issues.